2012
DOI: 10.1111/chd.12024
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Cerebral Circulation in Adults with Coarctation of the Aorta

Abstract: Prospective screening of adults with CoA confirmed the increased prevalence of IA but also identified increased age as the sole risk factor. These data suggested that screening is justified particularly in the fourth and fifth decades of life. Further studies are required that focus on the development, natural history, and treatment of IA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…18e21 Indeed, cardiac muscular arteries, aortic arch, and cervicocephalic arteries all originate from the neural ridge tissue, and the association between cardiac pathologies and IAs has been explained as a developmental abnormality of the neural ridge. 3,9,22,23 Although this relation between CofA and IAs has been suggested by several reports in the literature, most of them were potentially biased by confounding factors. The largest prospective study by Connolly et al 1 enrolled only adult patients, considerably older than ours (mean age No studies have evaluated so far a population of patients early treated in life to establish whether vascular abnormalities are truly developmental or acquired later because of multiple risk factors (hypertension, smoking and alcohol habit, lifestyle, etc.).…”
Section: Discussionmentioning
confidence: 84%
“…18e21 Indeed, cardiac muscular arteries, aortic arch, and cervicocephalic arteries all originate from the neural ridge tissue, and the association between cardiac pathologies and IAs has been explained as a developmental abnormality of the neural ridge. 3,9,22,23 Although this relation between CofA and IAs has been suggested by several reports in the literature, most of them were potentially biased by confounding factors. The largest prospective study by Connolly et al 1 enrolled only adult patients, considerably older than ours (mean age No studies have evaluated so far a population of patients early treated in life to establish whether vascular abnormalities are truly developmental or acquired later because of multiple risk factors (hypertension, smoking and alcohol habit, lifestyle, etc.).…”
Section: Discussionmentioning
confidence: 84%
“…In prior CHD case reports, intracranial aneurysms or the presenting CVA are mostly described in patients with CoA, and sometimes in patients with cyanotic CHD, such as truncus arteriosus, transposition of great arteries. [8][9][10][11][12][13][22][23][24] The embryological basis for such association between CoA (or other CHD) and intracranial aneurysm remains unclear. Besides, we also found that age was a risk factor for CVA in the whole CHD cohort.…”
Section: Discussionmentioning
confidence: 99%
“…10 By prospective CT angiographic evaluation, intracranial aneurysm was noted in 11% out of 43 adult CoA patients. 8 CoA patients may even present with aneurysmal cerebral or subarachnoid hemorrhage. [11][12][13] Given all these findings, we may suggest that hypertension in CoA patients, who have systemic arteriopathy, further increases the risk of CVA and should be aggressively controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanoticus betegekben a stroke előfordulása 4-14% [9,10]. A stroke a vezető halálok coarctatio aortaes betegekben is, de a magas számban társuló intracranialis aneurysma is jelentősen növeli e betegeknél a neurológi-ai szövődményeket [11,12]. Cerebrovascularis történé-sek magas számban fordulnak még elő ASD, Senningműtött nagyér-transzpozíciós betegeknél "residualis baffle leak" esetén, Fontan-keringésben és mechanikus műbillentyű beültetése után [8].…”
Section: Megbeszélésunclassified